2009
DOI: 10.1038/sj.bjc.6605438
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with interleukin-2 in malignant pleural mesothelioma: immunological and angiogenetic assessment and prognostic impact

Abstract: BACKGROUND: Administration of interleukin-2 (IL-2) has shown some effects on malignant pleural mesothelioma (MPM) tumour regression. The purpose of this study was to investigate the ability of IL-2 to modify immunological effector cells and angiogenesis in MPM patients and their prognostic value. METHODS: Tumour-infiltrating lymphocytes (CD4, CD8, Foxp3), mast cells (MCs) (tryptase and chymase), microvessel count (MVC) and VEGF were determined by immunohistochemistry in two series of MPM patients: 60 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 48 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…31 A recent study reported that IL-2 treatment lead to a reduced angiogenesis in subjects with malignant pleural mesothelioma. 32 Moreover, the aqueous humor level of IL-2 was significantly lower in patients with recurrent choroidal neovascularization and macular edema. 33 These findings indicated the antiangiogenetic effect of IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent study reported that IL-2 treatment lead to a reduced angiogenesis in subjects with malignant pleural mesothelioma. 32 Moreover, the aqueous humor level of IL-2 was significantly lower in patients with recurrent choroidal neovascularization and macular edema. 33 These findings indicated the antiangiogenetic effect of IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…While phase II intrapleural IL-2 has demonstrated some effectiveness in treating MPM, other routes of administration (intravenous and/or subcutaneous) as first-line treatment have failed to do so [114,115]. In a group of 60 MPM patients who received pre-operative intrapleural IL-2 treatment, a significantly higher number of T regs was observed in surgical specimens, as compared to 33 patients who did not receive IL-2 [116]. Within the IL-2-treated group, high T regs , defined as greater than the median on immunohistochemical assessment, was correlated with both decreased patient survival and increased tumor recurrence on subgroup analysis.…”
Section: Human Immunotherapy Trialsmentioning
confidence: 99%
“…45 Histological findings were reviewed treatment. [14][15][16][17] Several studies have also been performed with interferons (IFN) (α, β and γ), and in particular, it has been demonstrated that patients treated with IFNβ have an increased survival, based on the dual action of interferon on both immune and tumor cells. 18 In addition, new and potentially effective treatments have been reported with either the active, where one or several antigens are used for triggering an immune response, or the passive immunotherapy, which relies on effector cells, isolated and activated in vitro before their re-injection in vivo.…”
Section: Resultsmentioning
confidence: 99%